How to Prepare Brain Specimen for White Fiber Dissection: An Illustrative Guide - Sharma, Diksha; Agrawal, Deepak (Indian Journal of Neurotrauma, 2025)
White fiber dissection is a method in acquiring in-depth neuroanatomical understanding for surgical practice. Collection of brain specimen during autopsy and preparation of the brain specimen without any disruption in anatomy are essential steps as cadaveric brain dissection is an important part of neuroanatomical teaching, and it further provides an initiative of how kind and precise the dissection must be during live surgery.The aim of the study was to explain the stepwise technique of the preparation of the brain specimen for white fiber dissection as relevant to neuroanatomical and neurosurgical teaching.The brain removal procedure is performed on the human brain during the conventional autopsy process.Various consecutive and typical steps are recommended for the removal and preparation of the specimen. Photographs accompany each relevant step for better understanding of the procedure.In this article, we describe the technique and step-by-step guidelines to effectively remove the brain and to prepare the brain specimen for white fiber dissection. Avoiding common errors during this intricate procedure saves time and brain specimens.
Keywords: brain removal; brain specimen; Klingler's technique; white fiber dissection; white matter anatomy